Strategic Planning of National Development: International and Ukrainian Experience. Part II. National Experience of Strategic Planning in Ukraine - Kulak А. O.; Sitnikova, N. P. (Statistics of Ukraine, 2024)
The article addresses the issues of strategic planning for national development over the long term, specifically presenting an analysis of international experience and the current state of domestic strategic planning. It discusses the legislative framework and experience in developing long-term strategies for national and sustainable development. The second part of the article provides an overview of domestic practices in strategic planning, including a review of the legal framework, a retrospective examination of the development of long-term national development strategies, and strategic documents on sustainable development. It also highlights the current state of strategic planning in Ukraine. The author emphasizes the urgent need to improve the national system of state strategic planning by incorporating the experience of other countries and best international practices. Considerable attention is given to the challenges in the long-term segment of strategic planning for national development. The article asserts the necessity of modernizing the legislative framework, employing a participatory approach to engage citizens and stakeholders, introducing digital technologies in monitoring processes, and revising evaluation requirements. The planning process should adhere to the principles of results-based management and be grounded in evidence, facts, and qualitative data at both the planning and monitoring and evaluation stages. The long-term national development strategy of Ukraine can serve as the core of an updated system of strategic documents and a guideline for making evidence-based decisions. The long-term strategy should fulfill several key functions, such as goal-setting, coordination, integration, regulation, and guidance. In conclusion, the article finds it advisable to improve strategic planning in Ukraine to ensure sustainable development, even amidst the current challenges of transitioning from recovery to development.